2005
DOI: 10.1016/j.devcel.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Integrinα5 and Delta/Notch Signaling Have Complementary Spatiotemporal Requirements during Zebrafish Somitogenesis

Abstract: Somitogenesis is the process by which the segmented precursors of the skeletal muscle and vertebral column are generated during vertebrate embryogenesis. While somitogenesis appears to be a serially homologous, reiterative process, we find that there are differences between the genetic control of early/anterior and late/posterior somitogenesis. We demonstrate that point mutations can cause segmentation defects in either the anterior, middle, or posterior somites in the zebrafish. We find that mutations in zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(192 citation statements)
references
References 62 publications
11
181
0
Order By: Relevance
“…In Xenopus, ECM and, in particular, fibronectin have been shown to play important roles in directing anterior mesoderm migration (39). A similar role for ECM in fish appears unlikely because the two fibronectin orthologues are not expressed on the track of the prechordal plate and the corresponding loss of functions, or integrin α5 loss of function, do not affect prechordal plate migration (40,41). Consistently, ECM (fibronectin and laminin) is first detected in the embryo at 65% epiboly, when the prechordal plate has already started its movement (42).…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus, ECM and, in particular, fibronectin have been shown to play important roles in directing anterior mesoderm migration (39). A similar role for ECM in fish appears unlikely because the two fibronectin orthologues are not expressed on the track of the prechordal plate and the corresponding loss of functions, or integrin α5 loss of function, do not affect prechordal plate migration (40,41). Consistently, ECM (fibronectin and laminin) is first detected in the embryo at 65% epiboly, when the prechordal plate has already started its movement (42).…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is found at chick (Duband et al, 1987) and zebrafish (Crawford et al, 2003) somite boundaries; in the latter case their accumulation is dependent on integrinalpha5 (Julich et al, 2005;Koshida et al, 2005). In zebrafish embryos deficient for both fibronectin and integrinalpha5, somite boundaries are initially formed but are not maintained, suggesting their role in boundary maintenance (Koshida et al, 2005).…”
Section: Local Quantitative Framework Of the Somite Microenvironmentmentioning
confidence: 99%
“…However, it is known that anterior somites, also known as cranial somites, are somewhat smaller than later stage somites and that they degenerate by the onset of metamorphosis. In addition, it has recently been found in zebrafish that different molecular signaling processes govern the formation of anterior and posterior somites (Julich et al, 2005). Thus it is possible that different sets or subsets of cell behaviors are responsible for forming somites at the anterior and posterior ends of the X. laevis embryo.…”
Section: Relative Timing Of Cell Behaviors During Rotation and Segmenmentioning
confidence: 99%
“…Oates and Ha (2002) showed that, although the Delta/ Notch signaling pathway is required for the formation of somites along the entire axis, the formation of anterior somites also requires the activity of her 7, a downstream target of the Notch signaling pathway. In addition, it has been shown that integrin ␣5 is required for the formation of anterior, but not posterior somites (Julich et al, 2005). How these molecular differences translate into the patterning and functional differences among somites remains unclear.…”
Section: Differences In Somite Morphogenesis Along the Anteroposteriomentioning
confidence: 99%